(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
This article explores the roots of the Canadian community service-learning (CSL) movement through a comparative discussion of service-learning in Canada and the United States. The article provides a brief overview of CSL’s historical foundations in both countries, addressing especially how differences in CSL funding infrastructure have distinctly shaped the movement in each country. While national funding bodies and nation-wide institutionalization remain central to CSL in the U.S., Canada’s CSL efforts have predominantly been shaped by the efforts of private foundations and grassroots community agents. This essay analyzes the obstacles and problems currently within Canadian CSL, but also provides recommendations around documentation, sustainability, and the future of CSL in Canada, including the recommendation to maintain a community first approach in Canadian CSL. As it considers how the influence of the United States continues to shape CSL in Canada, and how the two national movements remain distinct from one another, we hope this examination will contribute an historical perspective to scholarship on Canadian CSL and will offer entry points to engage in critical conversations on the emergence of the field.